PUSAT KEBUDAYAAN SEBAGAI WADAH SENI PERTUNJUKAN DENGAN PENDEKATAN GENIUS LOCI DI KOTAGEDE - Rud Yoneko Tunggadewi; Hardiyati Hardiyati; Kusumaningdyah Nurul Handayani (Universitas Sebelas Maret Surakarta, 2016)
Sustainability of cultural heritage in Yogyakarta continues to face barriers, those are partly due to the result of natural disasters, economic pressure, space requirements for modern activities and the lack of understanding and concern of the local community to the cultural heritage owned. Kotagede is one of Yogyakarta's cultural image-forming spot that still has diverse cultural heritage, which includes traditional house and performing art groups. Cultural Center presents as an effort of conservation, utilization, and development to maintain the sustainability of cultural heritage in Kotagede. The designing problems to solve are regarding with the concept of zoning and transforming Kotagede traditional house as a place of performing art activities, as well as with regard to the concept of circulation, transportation, nodes, and paths to connect them. Genius Loci is deployed to preserve the historical value, uniqueness, and authenticity owned by Kotagede. Genius Loci is the soul of a place that can be felt through identification and orientation towards the boundaries. As the object of planning and designing is a conserved traditional house, Infill Design conservation is employed as a technical method in the designing process. Infill Design conservation divides the traditional house into three zones i. e. critical, important, and contributory zone. The methods consist of issue and idea study, site determination, study of literature, problem statement formulation, approach analysis, macro, mezzo, and micro zone analysis, and the result of data analysis which is presented in the form of concept. The concept of macro scale includes the concept of circulation, transportation, and the role and position of the cultural center on the structure of Kotagede Cultural Heritage Site. The mezzo-scale concept includes the concept of zone-sequence. In each sequence, some activities and places of performing art activities will be selected based on their Genius Loci. The micro scale concept includes Infill Design of spatiality, structure, and utility by concerning the form, color, and original material of the roof, walls and floor. Keywords: Cultural Center, Infill Design, Genius Loci, Kotagede, Traditional House, Traditional Performing Art